(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
While marketing scholars have emphasized the importance of informational influence, our understanding of how influential unfavorable information is still remains fragmental. The purpose of this study is to examine the direct and indirect impact of negative informational influence on consumer attitude toward e-commerce acceptance. We seek to prove that negative information about an e-vendor is composed largely of unfavorable reviews regarding product quality, product price, vendor’s after-sales service, and vendor’s trustworthiness, and not only has a direct effect on consumers’ attitude toward the acceptance of that e-vendor, but also has an indirect effect on such attitude via their detrimental beliefs of perceived product quality, perceived price, perceived after-sales service, and consumer trust in vendor. Detailed findings and implications for academics and practitioners are presented